La maîtrise d’ouvrage de Jean de France, duc de Berry (1340-1416). Reconstitution et analyse critique d’une documentation dispersée - Thomas Rapin (Tabularia)
A closed study of John of Berry’s archives can be usefull to understand his building mastery: a vast subject that cannot be limited to the most famous residences, e.g. the castle of Mehun-sur-Yèvre, or the ambitious political building scheme for the Sainte-Chapelle at Bourges. The number and diverse character of each building project required the mobilisation of every available man, from the modest castellan to the most important court officer, from the local craftsman to the most skilled and qualified stone mason. The construction of a building and its ensuing maintenance were closely linked. Since they formed part of the ducal administation, their interconnection explains the character of the documentary archive which is irregular, disorganised and incomplete.